Between desirability and reality: Conceptualization, measurement, causes, and consequences of overemployment - Julia Hiemer (University of Bamberg Press, 2022)
Overemployment, i.e., the preference for fewer work hours, is a widespread phenomenon in western societies, which may have negative consequences for individual well-being and organizational functioning. Previously overemployment has been defi ned from an economic perspective mainly as a time-money trade-off problem. This work is the first to adopt a psychological and subjectivist view on overemployment. Over three research projects a theory of overemployment, its causes and consequences is constructed and tested. In addition, a multidimensional overemployment scale is developed and initially validated. The three research projects include: fi rst, a review on overemployment conceptualizations and measurements; second, a Grounded Theory interview study with the aim to develop a theory on overemployment, its causes, and consequences; and third, a scale development study comprising over 1,400 participants over 4 studies. The importance of overemployment for individual well-being (e.g., burnout, job satisfaction), as well as for organizational variables (e.g., commitment, turnover intention) is shown. Overemployment is found to be a multidimensional construct consisting of three dimensions: length, density, and distribution of work time. The developed theory and scale will allow future researchers to analyze overemployment in more detail. The work offers interesting insights for HR and management practitioners when it comes to creating attractive working conditions.
Keywords: 330; Überbeschäftigung; Arbeitsbedingungen; Personalpolitik; Wohlbefinden; Arbeitszufriedenheit